The Secularization of Halal: State Bureaucracy vs Semantic Ethics in Indonesia’s Halal Governance - Rusli Rusli; Ubay Ubay; Murniati Ruslan; Maswani Maswani; Rizqi Handayani (AHKAM : Jurnal Ilmu Syariah, 2026)
A deeper conflict within Indonesia’s halal governance system is exposed by the controversy over halal certification for goods bearing names associated with haram concepts. This study examines the historical development of halal-certification organizations, sociological factors influencing halal assurance among producers and consumers, and the public response to the moral conundrum posed by halal-certified goods with names inappropriate to their religions, using a sociological–historical methodology. Primary data was gathered from documents and digital media sources using qualitative methods. The legal-semiotic anomaly appears in Law No. 33/2014 on Halal Product Assurance, where material consideration enables controversial names (such as haram, immoral, or occult elements) to be considered halal due to legal permissibility, creating a separation between halal as a material (legal) aspect and halal as an identity (semantic-ethical). The results show that this anomaly can be explained by an epistemic tension between positivist law and religious ethics, in which the former deems naming insignificant while the latter views the name as part of the meaning of halal. The problem lies in halal governance, where the notion of Halal-Identity is employed as a framework emphasising halal as an identity concept.   Abstrak Konflik mendalam dalam sistem tata kelola halal di Indonesia tampak dari kontroversi sertifikasi halal pada produk yang menggunakan nama berasosiasi dengan konsep ḥaram. Studi ini mengkaji perkembangan historis lembaga sertifikasi halal, faktor sosiologis yang memengaruhi jaminan halal di kalangan produsen dan konsumen, serta respons publik terhadap dilema moral dari produk bersertifikat halal dengan nama yang tidak sesuai secara keagamaan, menggunakan pendekatan sosiologis-historis. Data primer diperoleh dari dokumen dan media digital melalui metode kualitatif. Anomali legal-semiotik muncul dalam UU No. 33/2014 tentang Jaminan Produk Halal, di mana pertimbangan material memungkinkan nama kontroversial (seperti ḥaram, immoral, atau unsur okultisme) tetap dianggap halal karena sah secara hukum. Hal ini menciptakan pemisahan antara halal sebagai aspek material (legal) dan halal sebagai identitas (semantik-etis). Hasil penelitian menunjukkan bahwa anomali ini bersumber dari ketegangan epistemik antara hukum positivistik dan etika agama: yang pertama menganggap penamaan tidak relevan secara hukum, sementara yang kedua memandang nama sebagai bagian dari makna halal. Masalah ini menunjukkan bahwa konsep Halal-Identity diperlukan sebagai kerangka analisis yang menegaskan halal sebagai identitas yang utuh.